Digital Politics in the Diaspora: U.K. Aam Aadmi Party Supporters Online and Offline. (May 2020) - Webb, Martin
In 2012, the Aam Aadmi (common man) Party (AAP) made its debut on the Indian political scene on a platform promoting ethical politics, anticorruption action and active citizenship. Inspired by the AAP's call to "change politics, " many nonresident Indians (NRIs) in the U.K. Indian diaspora joined an international network of groups that provided support for the party in subsequent successful election campaigns. This article follows the ways in which digital media played a key role in the formation of intense individual attachments to the party, and how, for some, it became the means through which disillusionment with the party and its project was expressed. By attending to digital politics in the Indian diaspora as it plays out in this relatively recent political formation, we can gain a new perspective on the circulations, connections, and class values through which postliberalization projects to reform the nation are worked on from beyond its borders.